OCULAR GRAFT-VERSUS-HOST DISEASE - Prieto, Bárbara Leite de Souza; Rocha, Eduardo Melani; Trindade, Marilia; Serapicos, Patrícia; Souza, Rodrigo Guimarães de (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION